The Right Choice for Production Patterns to Minimize Cost of Incremental - Erick Wijaya; Sevenpri Candra; Haryadi Sarjono (Bina Nusantara University, 2011)
PT Damai Sejahtera Utama is a manufacturing company engaged in timber production. The company is processing wood sticks (logs) into plywood. The purpose of this research is to find the most efficient production patterns with the pattern approach 3 (three) of production, namely: Wavy production patterns, production patterns Constant, and Moderate production patterns. With this method is expected to determine the most appropriate production pattern with the condition of the company, so as to minimize Incremental costs that will occur. The results of this study indicate that by using corrugated production patterns can cause incremental cost of 3,330,267,500 IDR. For Constant production patterns can lead to costs amounting to 3,696,317,500 IDR whereas if the company uses pattern Moderate production costs to be incurred amounted to 3,289,417,500 IDR. From the results of this study showed that moderate production patterns have the smallest Incremental costs compared to the wavy or constant patterns of production.